herramienta Desarrollo de un Juego Serio para el tratamiento de la dislalia (Rotacismo) como didáctica de la carrera de Educación Especial de la UNL - Quizhpe Mendoza, Alexis David (2023)
The purpose of this Degree Project (DP) is to develop a reliable game, taking as a reference the activities used to correct the R phoneme, using the Unity video game engine to create the scenes based on the same exercises used in the treatment for rotacism dyslalia. With this, the following research question arises: How can we automate the activities performed in monitoring rotacism dyslalia through a serious game? We carried out the development of the serious game in the present DP in three phases. The first phase was for collecting data necessary to understand more about the treatments used in controlling dyslalia by rotacism, defining the activities to work with, and, at the same time, establishing the needed frame requirements for developing the serious game. In the second phase, we developed the serious game combining the methodology of Pere Marqués, which focused on the development of educational software, and the SUM methodology, which focused on the development of games; also, we did the coding in the game engine, Unity, with the C# programming language for the development of the scripts, and using the Node JS framework, the web service connected to MongoDB was developed for the management of the database. Finally, in the third phase, a test plan was established in which teachers and students of the Special Education career participated. An approval survey was applied to check the quality of the web service and the serious game, which allowed them to answer the research question formulated. Finally, we elaborated a set of recommendations for future work, considering the most relevant aspects of the project. Keywords: dyslalia, rotacism, serious game, SUM methodology, Pere Marques methodology, Unity.